A quasar microlensing event towards J1249+3449?. (29th September 2020) - De Paolis, F; Nucita, A A; Strafella, F; Licchelli, D; Ingrosso, G
ABSTRACT: We show that the optical flare event discovered by Graham et al. towards the active galactic nucleus J1249+3449 is fully consistent with being a quasar microlensing event due to a ≃0.1 M⊙ star, although other explanations, such as that, mainly supported by Graham et al., of being the electromagnetic counterpart associated with a binary black hole merger, cannot be completely excluded at present.